Paratesticular Rhabdomyosarcoma in Young Adult- A Case Report - NAVIN KUMAR SINHA (Journal of Clinical and Diagnostic Research, 2015)
Para testicular rhabdomyosarcoma is a rare malignant tumour, which usually presents as a painless mass in the scrotum or groin. A case of para testicular rhabdomyosarcoma in a 17-year-old male is being reported here who presented with chronic scrotal pain. Paratesticular rhabdomyosarcoma is a rare non germ cell tumour of scrotal sac in children and young adult/teens which can invade testis at presentation. Embryonal variant is the most common type. 40% cases can have metastasis to retroperitoneal lymph node. Diagnosis can be done on high degree of clinical suspicion coupled with biopsy and immunohistochemistry. Multimodality approach of treatment is often beneficial for patients.